High‐Resolution Field Mapping and Analysis of the August–October 2016 Coseismic Surface Faulting (Central Italy Earthquakes): Slip Distribution, Parameterization, and Comparison With Global Earthquakes. Issue 2 (1st February 2019) - Brozzetti, F.; Boncio, P.; Cirillo, D.; Ferrarini, F.; de Nardis, R.; Testa, A.; Liberi, F.; Lavecchia, G.
Abstract: We focus on the coseismic surface faulting exposed along the Mt. Vettore‐Mt. Bove fault system (VBF, central Italy), that activated during the 24 August 2016, Amatrice earthquake (Mw 6.0) and soon after reactivated during the 26 October Visso (Mw 5.9) and 30 October Norcia events (Mw 6.5 mainshock). We systematically recognized the coseismic surface ruptures of the aforesaid earthquakes, which document the repeated surface faulting on the same seismogenic structure in close temporal succession. We surveyed 1, 747 evidence of coseismic ruptures, 325 fault plane attitudes along the Vettoretto‐Redentore segment, and over 4, 000 data along the entire VBF that were organized in a GIS‐database. This data set allowed us to estimate the coseismic surface rupture length (SRL), maximum (MD) and average (AD) displacement associated with the Mw 6.0 and Mw 6.5 events. We found that the SRL and MD associated with the former are respectively 5.8 km and 28.5 cm and AD reaches 12.7 cm. For the mainshock, the values of SRL ≥ 22 km and MD = 222 cm were measured. The cumulative, post‐30 October parameters are SRL = 30 km, MD = 240 cm, AD = 36 cm. Despite that the MD of the Mw 6.0 event differs by 1 order of magnitude respect to the mainshock MD, the two slip profiles display a similar multiscale sinuosity showing a significant control of the long‐term fault segmentation on the coseismic rupturing. Comparing the obtained coseismic parameters with literature global earthquakes data highlights some peculiarities of the 2016 central Italy surface rupture pattern, which suggest caution in applying empirical relationships to highly segmented seismogenic faults. Key Points: Large data sets of coseismic ruptures, collected along the Mt. Vettore‐Bove fault after the 24 August and 30 October 2016 earthquakes, allow a comparison of the associate surface faulting Coseismic slip distribution reveals the segmentation pattern and hierarchical organization of a regional fault system in the Apennines Coseismic parameters of the surface rupture of Mt. Vettore‐Bove fault suggest caution in applying empirical regressions to segmented faults